FILANTROPI ISLAM DALAM PENINGKATAN EKONOMI UMAT - fadli, Fadli (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2016)
AbstractIs a basic principle of Islam that a Muslim who belongs to the financial / wealth commanded by God to share and help to his fellow Muslims. One charity, which has a system and a highly accurate and scalable to eradicate poverty from its roots and is binding because it is one of the pillars of religion must be carried out in accordance with the provisions of Islamic Sharia. Zakat is also highly charged social where it is a form of social responsibility of the owners of wealth to those who lack.The main value lies precisely zakat to the partisanship that very closely to those in need. It is an essential element in the process of distribution of wealth is the key to the prosperity of mankind. Because the purpose of Islamic economics is welfare of mankind as a whole, without exception, the Zakat plays a vital role in the economic system of Islam. So it is not foreign trsebut in Indonesia. For there are many institutions in Indonesia that help shade the aid of our example as: Amil Zakat Nasional (BAZNAS), Dompet Dhu'afa, Laziz, Foundation for Social Fund, Baitul Mal, Rumah Zakat, Islamic Bank, etc. Therefore, there was no obstacle or excuse us for not sharing with others.Keywords: philanthropy, zakat, charity